Globalization and internationalization in higher education : theoretical, strategic and management perspectives - Foskett, Nicholas, 1955-; Maringe, Felix (Continuum, 2010)
Universities all over the world are increasingly recognising the challenges of globalization and the pressures towards internationalization. This collection draws together a wealth of international experience to explore the emerging patterns of strategy and practice in internationalizing Higher Education. Questions considered include: How is the concept of globalization in the context of higher education understood by those who lead universities across the world? What new challenges are being created as universities seek to become more international? Which forms of leadership are needed and will be needed in the future in these transforming institutions and how are they going about preparing for and achieving this?